Two stripe rust effectors impair wheat resistance by suppressing import of host Fe–S protein into chloroplasts. Issue 4 (16th September 2021) - Wang, Xiaodong; Zhai, Tong; Zhang, Xingmin; Tang, Chunlei; Zhuang, Rui; Zhao, Haibin; Xu, Qiang; Cheng, Yulin; Wang, Jianfeng; Duplessis, Sébastien; Kang, Zhensheng; Wang, Xiaojie
Abstract: Several effectors from phytopathogens usually target various cell organelles to interfere with plant defenses, and they generally contain sequences that direct their translocation into organelles, such as chloroplasts. In this study, we characterized a different mechanism for effectors to attack chloroplasts in wheat ( Triticum aestivum ). Two effectors from Puccinia striiformis f. sp. tritici ( Pst ), Pst_4, and Pst_5, inhibit Bax-mediated cell death and plant immune responses, such as callose deposition and reactive oxygen species (ROS) accumulation. Gene silencing of the two effectors induced significant resistance to Pst, demonstrating that both effectors function as virulence factors of Pst . Although these two effectors have low sequence similarities and lack chloroplast transit peptides, they both interact with TaISP (wheat cytochrome b 6–f complex iron–sulfur subunit, a chloroplast protein encoded by nuclear gene) in the cytoplasm. Silencing of TaISP impaired wheat resistance to avirulent Pst and resulted in less accumulation of ROS. Heterogeneous expression of TaISP enhanced chloroplast-derived ROS accumulation in Nicotiana benthamiana . Co-localization in N. benthamiana and western blot assay of TaISP content in wheat chloroplasts show that both effectors suppressed TaISP from entering chloroplasts. We conclude that these biotrophic fungal effectors suppress plant defenses by disrupting the sorting of chloroplast protein, thereby limiting host ROS accumulation and promoting fungal pathogenicity. Abstract : Despite the lack of chloroplast transit peptide, rust effectors affect chloroplast-mediated defenses by suppressing import of host Fe–S protein to chloroplast to promote pathogenicity of stripe rust.